2018
DOI: 10.1111/pin.12621
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal follicular lymphoma: Current knowledge and future challenges

Abstract: The gastrointestinal (GI) tract is the most commonly involved site of extranodal follicular lymphoma (FL). GI-FL shows very indolent clinical behavior and localized at GI tract without any progression or transformation compared to nodal FL. The most frequently involved site of the GI tract was the duodenum followed by the jejunum and ileum, and only 15% of FL arising in the second part of the duodenum were localized there without scattered very small daughter lesions in other GI tract examined by double-balloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 44 publications
7
56
0
4
Order By: Relevance
“…Duodenal-type FL shows deviations in heavy chain variable (VH) usage, especially in VH4-34 and VH5. 7,8,12 We reported similar deviations in ocular adnexal and thyroid MALT lymphoma 16,17 ; this along with a previous report 18 suggests that duodenal FL is similar to MALT lymphoma. VH4-34 is not only specific to these lymphomas, but is also observed in some cases of hairy cell leukemia, its variant, 19 and splenic diffuse red pulp small B-cell lymphoma; interestingly, the former two lymphomas are thought to involve activated memory B cells.…”
Section: Similarities Between Duodenal-type Fl and Malt Lymphomasupporting
confidence: 82%
See 2 more Smart Citations
“…Duodenal-type FL shows deviations in heavy chain variable (VH) usage, especially in VH4-34 and VH5. 7,8,12 We reported similar deviations in ocular adnexal and thyroid MALT lymphoma 16,17 ; this along with a previous report 18 suggests that duodenal FL is similar to MALT lymphoma. VH4-34 is not only specific to these lymphomas, but is also observed in some cases of hairy cell leukemia, its variant, 19 and splenic diffuse red pulp small B-cell lymphoma; interestingly, the former two lymphomas are thought to involve activated memory B cells.…”
Section: Similarities Between Duodenal-type Fl and Malt Lymphomasupporting
confidence: 82%
“…In this series, 54 cases of duodenal origin were thoroughly examined by double‐balloon endoscopy; in most of these, very small daughter lesions were scattered in the small intestine, and only 15 cases showed FL in the duodenum alone (Fig. b) . Endoscopic mucosal resection was performed in some cases, revealing follicular (nodular) lesions and villi filled with small lymphoid cells (Fig.…”
Section: Establishment Of Duodenal‐type Flmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that small intestine, colon disease but not stomach disease is associated with longer OS in FL. Primary gastrointestinal FL is usually associated with an indolent clinical course has been proposed as a distinct clinicopathological entity (Takata et al , ). Few data are available regarding the impact of extranodal disease for SLL, BL, MCL and PTCL and this study may serve as basis for further evaluation.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Most cases of FL occur in the lymph nodes, and gastrointestinal FL (GI-FL) is the most common type of primary extranodal FL, accounting for 10% of all FLs. 1,2 With the recent increase in the diagnosis of GI-FL, 3 primary intestinal FL has been classified as a variant of FL in the World Health Organization (WHO) Classification, 4th Edition. 4 Macroscopically, GI-FL typically presents with multiple white nodules in the descending duodenum.…”
Section: Introductionmentioning
confidence: 99%